Back Cover: Reduced Graphene Oxide–Ag3PO4 Heterostructure: A Direct Z‐Scheme Photocatalyst for Augmented Photoreactivity and Stability (Chem. Asian J. 4/2016). Issue 4 (5th February 2016) - Samal, Alaka; Das, D. P.; Nanda, K. K.; Mishra, B. K.; Das, J.; Dash, A.
Abstract : A reduced graphene oxide–Ag3 PO4 (RGO–Ag3 PO4 ) heterostructure has been synthesized via a simple one‐pot photoreduction route. Complete organic dye mineralization in just five minutes and photocatalytic hydrogen production is demonstrated over the RGO–Ag3 PO4 heterostructure through a direct Z‐scheme electron transfer mechanism under visible‐light illumination. More information can be found in the Full Paper by D. P. Das et al. on page 584 in Issue 4, 2016 (DOI:10.1002/asia.201501286 ).